MEKANISME PEMBERHENTIAN KEPALA DAERAH BERDASARKAN PASAL 83 AYAT (1) UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH - Aminah, Siti (Wacana Hukum, 2018)
AbstractThe mechanism for removing The Head of local goverment from the Office based on Article 83 Subsection (1) of Law Number 23 Year 2014 on local Government begins with the status of a head of local goverment being charged with criminal offense, followed by temporary removal from his/her office based on a register at a Court. It is also found that the officer in charge of removing a Head of local goverment is the President for an offending Governor and a Minister for an offending Regent or Mayor, without the need for a consultation with the local House of Representatives. Meanwhile, the legal consequences of a removal of a Head of local goverment  that the offender’s rights and responsibilities are assumed by Vice Head of local goverment, until a legally binding verdict on the matter has been issued by the Court. Whenever a Head of local goverment being indicted is not removed from his/her office, then the President or the Minister concerned may be charged of unlawful conduct that cause legal uncertainties within the bureaucracy of the regional government involved. AbstrakMekanisme pemberhentian sementara Kepala Daerah berdasarkan Pasal 83 Ayat (1) Undang-Undang Nomor 23 Tahun 2014 tentang Pemerintahan Daerah harus diawali dengan adanya status seorang Kepala Daerah yang telah ditetapkan sebagai terdakwa dalam tindak pidana kejahatan, selanjutnya proses dilakukan pemberhentian sementara Kepala Daerah harus berdasarkan register perkara di Pengadilan dan yang berwenang untuk memberhentikan Kepala Daerah yang telah ditetapkan sebagai terdakwa ialah Presiden untuk gubernur, dan Menteri untuk Bupati atau Walikota tanpa melalui usulan Dewan Perwakilan Rakyat Daerah. Konsekuensi hukum diberhentikannya Kepala Daerah yang berstatus terdakwa ialah tugas, dan wewenang Kepala Daerah dilaksanakan oleh Wakil Kepala Daerah sampai dengan adanya putusan pengadilan yang telah memperoleh kekuatan hukum tetap, namun apabila Kepala Daerah yang telah ditetapkan sebagai terdakwa dalam tindak pidana tersebut tidak diberhentikan dari jabatannya maka Presiden dan Menteri dapat dianggap tidak patuh terhadap perintah undang-undang dan menyebabkan ketidakpastian hukum dalam birokrasi penyelenggaraan pemerintahan daerah di daerah tersebut.